Responding to a call to action for health equity curriculum development in pediatric graduate medical education: Design, implementation and early results of Leaders in Health Equity (LHE) - Hernandez, Raquel G.; Thompson, Darcy A.; Cowden, John D. (Frontiers in Pediatrics, 2022)
Introduction: Recent calls to action have urged graduate medical education leaders to develop health equity (HE)-focused curricula to redouble efforts to promote pediatric HE and address racism. Despite this call, examples of HE-focused curricula for pediatric residents are lacking. Such curricula could catalyze educational innovations to address training gaps. Objective: To describe the design, content, and delivery of “Leaders in Health Equity (LHE),” an innovative, HE-focused curriculum delivered to categorical pediatric residents using multi-modal, service-free retreats. Methods: This single institution, longitudinal curriculum study occurred between 2014-2020 and reports multi-level outcomes including: 1) impact on trainee’s HE related knowledge, skills and satisfaction, 2) residency impact and 3) institutional impact. Educational approaches used related to design, content and delivery are summarized and detailed. Results: Trainees (n=72) demonstrated significant improvements in pre-post knowledge and skills related to HE content. Residents also reported increased desire for advanced HE content over the course of the 6-year study period. Residency impact on operations and resources were sustainable with the opportunity for integration of LHE content in other curricular and training areas noted. Institutional impact included catalyzing organizational HE initiatives and observing an increase in resident-led quality improvement (QI) projects focused on LHE content. Conclusions: On-going adaptation and growth of LHE content to educate increasingly prepared pediatric trainees is a critical next step and a best practice for educators in this evolving field. Developing HE curricula within pediatric training programs using a longitudinal, leadership-centered approach may be an effective educational strategy in addressing pediatric health disparities.